The Moderating Role of Firm Value in the Effect of Profitability Ratios, Macroeconomics, and Firm Size on Financial Distress - Siti Elisah; Heliani (Politeknik Negeri Madiun, 2023)
One of the main contributors to the country's economic health is the banking industry. During 2017-2021, 8 banking companies were liquidated. So it needs to be anticipated from the start so that bankruptcy does not occur. One way to see if there is financial distress in a company can be done by using the Altman's Z-Score method. This study was conducted with the aim of measuring and knowing the extent of the influence of profitability, macroeconomics, and firm size on financial distress through a moderating variable in the form of firm value. This is a quantitative study that relies on secondary data collected through a literature review. The population of this study is the entire banking industry in Indonesia, with a total sample of 23 companies obtained using a purposive sampling approach. This study uses panel data using the Moderated Regression Analysis (MRA) approach, which was carried out using Econometric Views (Eviews) version 10. According to the findings of this study, profitability has a beneficial effect on financial distress, but macroeconomics, business size, and firm value no effect. While the firm value is considered unable to moderate the independent variable on the dependent variable in this study.